A Project-Based Learning Model Using 360° Ecotourism River Videos for Teaching English Speaking Skills - Fani, Armin; Nurdian, Novi; Setyawati, Novi Suma (Journey: Journal of English Language and Pedagogy, 2025)
The growing demand for communicative competence in English requires pedagogical models that offer authentic, situated language practice beyond conventional classroom instruction. This Research and Development (R&D) study, employing the ADDIE model, aims to design and evaluate a Project-Based Learning (PjBL) model integrated with 360° ecotourism river videos to enhance junior high school students’ English speaking skills. The development process involved needs analysis, product design, expert validation, and a small-group trial. The final product consisted of a 360° immersive video portraying the Lok Baintan Floating Market and an accompanying PjBL-based speaking module. Validation results indicated strong pedagogical viability, with ratings from a technology expert (73.4%), an English teacher (88.6%), and students during the trial phase (92.5%). Qualitative observations further revealed heightened student engagement and motivation during speaking tasks. These findings suggest that integrating immersive video with PjBL creates an authentic, low-anxiety environment conducive to meaningful oral communication. The study contributes to ELT pedagogy by demonstrating how immersive technology can operationalize situated learning principles within project-based speaking instruction while strengthening the use of local cultural content in English language teaching.